Evaluating the Impact of the Tolerance Village Initiative on Interfaith Harmony: A Case Study in Jamika, Bandung - Nurjannah, Nurjannah; Bin AB Rahim, Muhammad Nazmi (Prodi Studi Agama-Agama, 2024)
The concept of